STEM AND STEAM EDUCATION IN 1st DECADE: A BIBLIOMETRIC ANALYSIS (2014-2025) - Tupamahu, Pieter Zakarias; Dasari, Dadan; Priatna, Nanang; Lethulur, Nelma Dortje (Prodi Magister Pendidikan Matematika Pascasarjana Universitas Pattimura Ambon, 2025)
STEM and STEAM education has become a strategic learning approach in addressing global challenges in the Industrial Revolution 4.0 and Society 5.0 era, focusing on developing 21st-century skills, such as creativity, critical thinking, problem-solving and collaboration. This study used bibliometric analysis of 535 articles from the Scopus database published between 2014 and 2025 to explore research trends, dominant keywords, geographical contributions, and author and institutional impact. Data analysis conducted with RStudio, VOSviewer, and Excel identified four main clusters: skills development, educational approaches, utilization of STEM in various fields, and use of learning-based tools such as AR and VR. STEM and STEAM education effectively increased student engagement and built cross-disciplinary skills. However, challenges such as gaps in technology access and teacher training still need to be addressed. These results provide important insights for curriculum development, teacher professional training and education policies supporting technology-based learning transformation.